2020
DOI: 10.1101/2020.03.21.990770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent human neutralizing antibodies elicited by SARS-CoV-2 infection

Abstract: The pandemic caused by emerging coronavirus SARS-CoV-2 presents a serious global public health emergency in urgent need of prophylactic and therapeutic interventions. SARS-CoV-2 cellular entry depends on binding between the viral Spike protein receptor-binding domain (RBD) and the angiotensin converting enzyme 2 (ACE2) target cell receptor. Here, we report on the isolation and characterization of 206 RBD-specific monoclonal antibodies (mAbs) derived from single B cells of eight SARS-CoV-2 infected individuals.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
157
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 374 publications
(168 citation statements)
references
References 46 publications
6
157
0
5
Order By: Relevance
“…We showed RBD-SpyVLPs to be strongly immunogenic in mice and pigs, inducing high titre neutralising antibody responses against wild type SARS-CoV-2 virus. This study confirms that the RBD is the key immunogenic domain for eliciting neutralising monoclonal antibodies against SARS-CoV-2, in line with studies showing that highly neutralising antibodies isolated from convalescent patients bind to the RBD 16,26,38,[40][41][42][43][44][45][46] . We showed that RBD-SpyVLPs are recognised by a panel of mAbs isolated from convalescent patients 26 binding to various epitopes on the RBD (Figure 2A).…”
Section: Discussionsupporting
confidence: 84%
“…We showed RBD-SpyVLPs to be strongly immunogenic in mice and pigs, inducing high titre neutralising antibody responses against wild type SARS-CoV-2 virus. This study confirms that the RBD is the key immunogenic domain for eliciting neutralising monoclonal antibodies against SARS-CoV-2, in line with studies showing that highly neutralising antibodies isolated from convalescent patients bind to the RBD 16,26,38,[40][41][42][43][44][45][46] . We showed that RBD-SpyVLPs are recognised by a panel of mAbs isolated from convalescent patients 26 binding to various epitopes on the RBD (Figure 2A).…”
Section: Discussionsupporting
confidence: 84%
“…Plaque reduction neutralization tests are the gold standard for assessing neutralizing ability, [23][24][25][26] and ongoing studies are in progress to confirm anti-RBD antibodies are neutralizing in SARS-CoV-2 infection. 27 Some commercially available assays measure the more abundant nucleocapsid protein, which may increase sensitivity to detect a serologic response early in the course of infection, therefore, shifting the seroconversion curve to the left. However, antibodies to nucleocapsid protein are unlikely to provide protective immunity as nucleocapsid protein is inaccessible to antibodies in an intact virus.…”
Section: Negative Results Do Not Completely Preclude Sars-cov-2mentioning
confidence: 99%
“…Recent studies have shown that related, potently neutralizing monoclonal antibodies that recognize the SARS-CoV-2 receptor binding domain (RBD) are often elicited in SARS-CoV-2 infection (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). These antibodies have great potential to be clinically impactful in the treatment and prevention of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%